Professor Edgeworth's View on Index-Numbers - Walsh, C. M. (Quarterly Journal of Economics, 1924)
Journal Article Professor Edgeworth's Views on Index—Numbers Get access C. M. Walsh C. M. Walsh Bellport, N. Y. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 38, Issue 3, May 1924, Pages 500–519, https://doi.org/10.2307/1882334 Published: 01 May 1924